Dealing with polarization in schools: reflective and deliberative practices - Claudio Melacarne; Marina Slavutzky (University of Bologna, 2023)
Polarization and various extremist movements are on the rise and young people's exposure to propaganda, disinformation, racism and hate speech has increased (Benjamin et al., 2021). Not only the society tends to be more polarized, but there is mounting concern that social media sites contribute to it by creating echo chambers that insulate people from opposing views about current events (Bail et al., 2018; Kubin and von Sikorski, 2021). Since teachers are at the forefront of these trends, they get to witness and address first-hand the effects and consequences that the various polarized ideologies may have on youth. Therefore, developing a global perspective that allows students to participate in an interconnected world, understand different viewpoints, learn to dialogue, value other cultures, and benefit from interculturality has become the objectives of world educational policy (Azqueta and Menino Arribas, 2020). The aim of this paper is to discuss the topic of polarization and then focus on two socio-pedagogical frameworks that are useful in this field: deliberative theory and reflexive practices.